Rituais de cuidado desenvolvidos por famílias no processo gestacional: um estudo etnográfico - Prates, Lisie Alende (2017)
The gestational process represents a milestone in the cycle of family development, which can be perceived and lived according to each family culture. Understanding the gestational process as a family event, it is clear that the rituals of social transition, at this stage, do not involve just the woman, but the whole family and have as their purpose to provide care to the woman-baby-family triad. In this perspective, is presented as a research question: what are the rituals of care developed by the family in the gestational process? The objective of this research was to know the rituals of care developed by the family in the gestational process. This is an ethnographic research, developed with eleven informants, of whom six were key informants and five general informants, during the year 2016, in a medium-sized city in the interior of the State of Rio Grande do Sul. It was adopted the model of Observation-Participation-Reflection (OPR). As data production techniques, participant observation and interview were used. The field diary was used to record data. Data analysis of the ethnographic survey was adopted. All ethical aspects of human research were respected, according to Resolution 466/2012, of the National Health Council. Data production started after project approval of Human Research Ethics Committee, under the CAAE 53928116.6.0000.5346. During the pregnancy, care rituals developed by the family involve the pregnancy disclosure, the feeding, the use of homeopathy and teas, besides the reorganization of the family, the preparation of the bedroom and the baby's clothing, the baby shower, the child's future choices, the sponsorship and the pregnancy record by albums. In preparation for childbirth, care rituals are linked, about everything, to choose by domicile, characterized as a ritual of separation of the family for the experience of this event. They also involve preparation rituals for the family and the eldest son for the experience of childbirth, as well as rituals of preparation of the domicile, of the body and mind of the woman, Feeding and physical activity, and related to the fate of the placenta. It is considered that the knowledge of the rituals of care developed in the gestational process of the families help in understanding the way of life and family culture, as well as providing support to health professionals to respect and value these rituals to watch the “pregnant family” and, in this direction, qualify prenatal care. It is hoped that this study may to promote the discussion about the rituals of care developed in the gestational process of the family. Rituals of care represent cultural issues essential for the care of pregnant women, And their identification and understanding may contribute to the practice of the nurse in the humanized care of the woman and her family. In teaching, it is intended to contribute to the construction of knowledge in the area of Nursing and in other professions, who assist women and their families, during the gestational process, reflection on the importance of valuing and the singularities of each family context.